POLICY PERSPECTIVES OF MITIGATION AND RECOVERY DURING COVID-19 PANDEMIC: A NARRATIVE REVIEW - Withanage Iresha Udayangani Jayawickrama; Weerapperuma Kankanamge Wijaya Sarathchandra Kumarawansa; Kapu Gamage Ravindra Vishwajith Pathirathna; Adikari Mudiyanselage Pamila Sadeeka Adikari; Yaddehige Jayanath Samarasinghe (Indonesian Journal of Health Administration, 2021)
Background: The world is in the grip of an unprecedented novel COVID-19 pandemic. These have resulted in massive impacts on humans as well as on economies invariably. Hence, planning for a future pandemic is vital in minimizing deleterious effects.Aims: The current review aimed to derive common policy perspectives that are important in future planning of a pandemic.Methods: A narrative review was conducted by searching published articles from PubMed, Medline, Scopus, CINAHL, and Google Scholar. Forty-eight articles were selected for the review.Results: The policy perspectives derived under mitigation were rearranged into surveillance, epidemiology, and lab activities. The policy perspectives under recovery derived were related to economy, supply chain management, sustainable and green concept, and health system.Conclusion: Understanding common policy perspectives is important in the mitigation and recovery planning of a pandemic with similar nature in the future. The spillover effects in response to the mitigation measures are deemed vital in planning mitigation and recovery measures for future pandemics. Global and regional resource sharing mechanisms are vital when a universal shortage of healthcare resources occurs.Keywords: mitigation, pandemic management, policy perspectives, recovery